Vividness and Transformation of Mental Images in Karate and Ballet. Issue 3 (December 2014) - Di Corrado, Donatella; Guarnera, Maria; Quartiroli, Alessandro
While imagery research has become popular in recent years, little research has specifically investigated differences in imagery ability between open- and closed-skill sport activities. The purpose of this study was to investigate whether the type of task, open or closed, affects vividness and controllability differently. Thirty female classic dancers (closed skill), 30 female karate athletes (open skill), and 30 female non-athlete students, between 14 and 20 years of age ( M = 17.0, SD = 1.6), participated. They completed the Vividness of Visual Imagery Questionnaire, the Vividness of Movement Imagery Questionnaire, and the Subtraction of Parts Task. There was no difference in imagery ability between open- and closed-skill sport groups. Furthermore, dancers and karatekas had higher mean scores on imagery ability than the non-athlete group. A positive correlation was observed between the two questionnaires, supporting findings on the componential basis of imagery. This study contributed to increase the research in the specific area of open- and closed-skill sports and imagery ability.